Rietveld refinement, morphology and optical properties of (Ba 1-xSrx)MoO4 crystals - Nogueira, I. C.; Cavalcante, L. S. [UNESP]; Pereira, P. F S; De Jesus, M. M.; Rivas Mercury, J. M.; Batista, N. C.; Li, M. Siu; Longo, Elson [UNESP] (International Union of Crystallography (IUCr), 2013)
In this article, the structural refinement, morphology and optical properties of barium strontium molybdate [(Ba1-x Sr x )MoO4 with x = 0, 0.25, 0.50, 0.75 and 1] crystals, synthesized by the co-precipitation (drop-by-drop) method, are reported. The crystals obtained were structurally characterized by X-ray diffraction (XRD), Rietveld refinement, and Fourier transform-Raman (FT-Raman) and Fourier transform-infrared (FT-IR) spectroscopies. The shapes of the crystals were observed by means of field-emission scanning electron microscopy (FE-SEM). The optical properties were investigated using ultraviolet-visible (UV-Vis) absorption spectroscopy and photoluminescence (PL) measurements. XRD patterns, Rietveld refinement, and FT-Raman and FT-IR spectra showed that all of the crystals are monophasic with a scheelite-type tetragonal structure. The refined lattice parameters and atomic positions were employed to model the [BaO8], [SrO8] and [MoO4] clusters in the tetragonal lattices. The FE-SEM images indicate that increased x content produces a decrease in the crystal size and modifications in the crystal shape. UV-Vis spectra indicated a decrease in the optical band gap with an increase in x in the (Ba1-x Sr x )MoO4 crystals. Finally, a decrease in the intensity of PL emission is apparent with an increase in x up to 0.75 in the (Ba1-x Sr x )MoO4 crystal lattice when excited by a wavelength of 350nm, probably associated with the degree of structural order-disorder. © 2013 International Union of Crystallography Printed in Singapore - all rights reserved.
Keywords: Ba arrange=1-x Sr x)MoO4; clusters; co-precipitation; photoluminescence; Rietveld refinement; Field emission scanning electron microscopy; Fourier transform infra reds; Photoluminescence measurements; Strontium molybdate; Structural refinement; Tetragonal lattices; Tetragonal structure; Coprecipitation; Crystal structure; Drops; Enamels; Morphology; Optical properties; Photoluminescence; Strontium compounds; Tungstate minerals; X ray diffraction